Marketing Communication Strategy Through Social Media Instagram @tntbeautyofficial - Velia, Natasha; Nuraryo, Imam (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
On these days, technology has a significant progress which caused the business competition is also getting tougher. To be able to compete with other business, they need a good marketing communication strategy by utilizing the technology development itself. The research was conducted to determine the role of marketing communication strategies in forming a well-known business. Based on internet marketing theory, they used internet in order to promote their business and maintain long relationship with consumers. This research method is descriptive qualitative and data collection technique from observation, documentation, and direct interview. The results of the research shows that marketing communication strategies which has been carried out by TnT Beauty Shop through social media Instagram @tntbeautyofficial are personal selling, sales promotion, and public relations. They actively create various contents such as informative content, promotional content, and other content in order to make their followers feel more confident in buying the products. So it was concluded that the role of marketing communication strategies through social media Instagram has become one of important tools to carry out TnT Beauty Shop.